KORELASI PERILAKU CLIPERDIK DETERMINAN PENYAKIT TIDAK MENULAR DIABETES MELETUS DI WILAYAH KERJA PUSKESMAS PANCUR BATU DESA TANJUNG ANOM KECAMATAN PANCUR BATU KABUPATEN DI SERDANG - Magda Siringo-ringo; Dian Esvani Manurung; Yisica Oktaviani Manullang (STIKes Santa Elisabeth Medan, 2018)
Non-communicable diseases of diabetes eruption are a group of metabolic disorders with characteristics of insulin secretion which results in abnormal fat protein carbohydrates caused by several non-modifiable factors, namely; the age of genetic sex and which can be changed (and modificable./ covers the environment, in terms of consumption of lifestyle chemicals that are less active sports / physical activity obesity/obesity. lack of sleep rest, smoking consumption of foods high in cholesterol, prolonged stress prolonged hypertension blood knowledge that is less pregnancy. Goals : Research Objectives to analyze the correlation between behavioral determinants in terms of health checks regarding body mass index abdominal circumference blood pressure cholesterol). Methods : Research type Explanatory Survey cross-sectional approach. The number of 66 people with a simple random technique. Data is obtained through Questionnaires (IPAQ). A balanced healthy diet uses the frequency of the food Questionnaires (FFQ). Sleep quality instrument (Pittsburgh Sleep Quality Index 2 (PSQI) control stress using Scale Hamilton Anxiety rating (HARS). The occurrence of non-communicable diabetes using glucometer measurements. Data analysis of correlation rank spearmen technique and simple linear regression. Result : The results showed body mass index, abdominal circumference. High blood pressure and systolic and diastolic blood levels) Diligent exercise / physical activity (r = 0.847 - 0.809; P = 0.000), while strong positive correlation with significant strength is; carbohydrate consumption, fat protein (r = 0.770; P = 0.000), vegetable fruit fiber consumption and sleep rest correlation were quite strong with significantly weak (r = 0.289 - 0.598: P = 0.000 - & 0.009). Strees control did not have a strong negative correlation with a strong significance (r - 0.457; P = 0.000) with the incidence of non-communicable diabetes erupting. Concultion : It is recommended to the community, especially the Dusun VI residents of Tanjung Anom Village, to increase efforts to live healthy lives in diabetes screening in hospitals, clinics, laboratories, and Posbindu